Fibroblasts: Heterogeneous Cells With Potential in Regenerative Therapy for Scarless Wound Healing - Zou, Ming-Li; Teng, Ying-Ying; Wu, Jun-Jie; Liu, Si-Yu; Tang, Xiao-Yu; Jia, Yuan; Chen, Zhong-Hua; Zhang, Kai-Wen; Sun, Zi-Li; Li, Xia; Ye, Jun-Xing; Xu, Rui-Sheng; et al. (Frontiers in Cell and Developmental Biology, 2021)
In recent years, research on wound healing has become increasingly in-depth, but the therapeutic effect is still not satisfactory. Pathological tissue repair occurs from time to time. Influencing factors have been proposed, but it is difficult to find the turning point. Therefore, we focus our attention at the most basic level that is involved in tissue repair: fibroblasts. Fibroblasts were once considered terminally differentiated cells that represent a single form of cells, and their heterogeneity was not studied until recently. We believe that subpopulations of fibroblasts play different roles in tissue repair that result in different repair results, such as the formation of normal scars in physiological tissue repair and fibrosis or ulcers in pathological tissue repair. At the same time, it is proposed that scarless healing can be achieved by regulating fibroblast subpopulations.